Colombian evidence on REIT performance against inflation - Rincón Díaz, Sebastián David (2017)
Securitization through real estate investment trust funds (REIT) in the Colombian market remain an under researched topic, given their short history regarding data. New sources of information raise new and interesting questions concerning its usage. This study evaluates the available data regarding REIT’s, how international studies have approached to its analysis, and if previous findings in other markets reflects also in the Colombian market. Basically, this study analyzes how REIT’s behave with inflation, and a priori hypothesis might tell us that inflation and REIT’s are cointegrated in the long run, through the channel of rental income contracts, which have a pre-established periodical increase attached to the inflation